(untitled) (Annual of the Faculty of Philosophy in Skopje, 2011)
The article puts emphasis on critical thinking and its importance in organizing and realization of the process of teaching and learning in higher education. Having in mind contemporary reform changes which were initiated with the documents of the Bologna process, the aims and objectives of higher education are reexamined, which means knowledge, skills and abilities that students should develop during their academic life. Then follows a brief historical review of the characteristics and conditions for realization of the university teaching during the period of fifty year free development of higher education in Macedonia as a necessary context for the presence of critical thinking in students ’ teaching and learning. The main attention in the article is focused on creating environment for critical thinking in higher education, which is examined on a macro and micro level. On one hand, several key priorities regarding the organization of teaching and the role of the university teacher are elaborated. On the other hand, critical thinking is regarded as a key element of the classroom activities. Therefore, several conditions for its encouragement are indicated and analyzed.